Knowledge, Attitudes and Precautions Towards COVID-19 Pandemic among Bangladeshi Population: A Cross-Sectional Study - Kabir, Md Alamgir; Jhuma, Tania Akter; Islam, Muhammad Rashedul (Bangladesh Pharmaceutical Journal, 2023)
In response to COVID-19 emergency outbreak, several countries took unprecedented measures and lockdown was implemented worldwide to minimize the drastic consequences. To reduce the damage, collaboration and acquiescence of people is needed to limit the spread of the virus. This study attempted to assess the knowledge, attitudes and precautions taken against COVID-19 among the Bangladeshi people. An online survey was carried out between 12th April and 4th May, 2020 using a snowball sampling technique in which 424 Bangladeshi residents participated. Descriptive statistics, chi-square test, fisher’s exact test, one-way ANOVA, binary logistic regression, t-tests have been carried out. Most of the participants were concerned about the risk of COVID-19 as more than 80% people took 14 out of 18 precautions to avoid COVID-19. The attitudes toward COVID-19 showed people’s willingness to follow government guidelines on isolation (96.7%) and quarantine (97.6%). The overall mean knowledge score was 3.11 out of 4. According to the independent sample t-test, age distribution was significantly (p<0.05) associated with knowledge level of the participants. Overall participants had a good understanding of the COVID-19 and a positive attitude towards preventive measures. The basic knowledge on COVID-19 among the people is acceptable which indicates that the timely dissemination of the information by the government of Bangladesh had a positive impact on people’s behavior. Bangladesh Pharmaceutical Journal 26(1): 56-66, 2023 (January)